Development of a dynamic simulation code for the sulfur–iodine process coupled to a very high-temperature gas-cooled nuclear reactor. (February 2013) - Chang, Jiwoon; Shin, Youngjoon; Lee, Kiyoung; Kim, Yongwan; Youn, Cheong
One of the key issues in developing a sulfur–iodine (SI) thermochemical hydrogen production technology is how to operate the SI process, including the start-up operation procedure. In order to effectively establish a start-up procedure, it is necessary to develop a dynamic simulation code that can analyze the dynamic behavior of the SI process. Furthermore, a dynamic simulation is necessary for identifying the transient behaviors of the SI process by abnormal operation occurrences, which is a nuclear hydrogen process, coupled to a very high temperature gas-cooled reactor (VHTR) through an intermediate heat exchanger (IHX). In this paper, a VHTR-based SI process coupling system for a dynamic simulation code development is introduced. Component and integration modules for a dynamic simulation program including input/output graphical user interface (GUI) modules are also described, and the start-up dynamic behaviors of the SI process have been anticipated using the simulation code developed in this study. The GUI system of the dynamic simulation program, which has been developed using ChartFX and Spread 7.0, allows users to easily manage the I/O data generated from the dynamic simulation program of the SI process.